Does equal pay legislation reduce labour market inequality? - Leo Kaas (Institute for the Study of Labor (IZA), 2006)
This paper considers a labour market model of monopsonistic competition with taste-based discrimination against minority workers to study the effect of equal pay legislation on labour market inequality. When the taste for discrimination is small or competition is weak, the policy removes job segregation and the wage gap completely. However, with a bigger taste for discrimination or stronger competition, equal pay legislation leads to more job segregation, and sometimes minority workers end up earning less than before. Profits of discriminating firms may increase, and discrimination can persist in the long run although it would have disappeared without the policy.
urn:nbn:de:101:1-2009030978
Keywords: 330